Qualidade de vida relacionada à saúde bucal de indivíduos com mucopolissacaridoses: um estudo transversal pareado - Tahyná Duda Deps Almeida (2019)
Mucopolysaccharidosis (MPS) is a group of genetic metabolic diseases caused by an enzymatic inadequacy in lysosomes of the organism related to inborn errors of metabolism. It involves various physical, motor and intellectual abnormalities. Among the physical alterations, many are present in the face and in the oral cavity. There are few studies in the area of dentistry dedicated to MPS, and information regarding the oral characteristics present in those diagnosed with the disease and the impact that these characteristics can have on the oral health related quality of life of such of such individuals remains insufficient. This study aimed to compare the perception of the parents / caregivers of individuals with MPS and without MPS regarding the oral health related quality of life (OHRQoL) of of these individuals. A paired cross-sectional study was performed of 29 individuals with MPS and 29 without MPS, age from 3 to 21 years, and the parents/ caregivers. All the parents / caregivers of individuals with MPS attended by two reference hospitals in MPS care in Belo Horizonte, southeastern of Brazil, were invited to participate in the study. Individuals without MPS were selected at the pediatric and adolescent clinic of both hospitals. Data collection was carried out in one of the clinics of the Faculty of Dentistry of Federal University of Minas Gerais. The parents / caregivers respond to a structured questionnaire addressing issues related to the study theme and the short Brazilian version of the Parental-Caregiver Perceptions Questionnaire (P-CPQ), which measures the children's OHRQoL from the perspective of the parents. The researcher then performed the clinical examination of individuals with MPS and without MPS and investigated the following conditions: malocclusion, dental caries and oral hygiene. The examiner was previously calibrated, presenting kappa values ranging from 0.76 to 0.98. The main study was conducted after the calibration and pilot study. Data were analyzed using the software Statistical Package for Social Science (SPSS) (version 21.0). The Research Ethics Committee of the Federal University of Minas Gerais approved the study. The results were presented by scientific manuscript. The mean age of the subjects examined was 12.1 years (± 4.2). The age range of the parents / caregivers ranged from 23 to 59 years, with a mean of 40.9 years (± 9.0). Comparing the results of the domains of oral symptoms, functional limitation, well-being and instrument total, there was a statistically significant association, regarding the perception of parents about negative impact of oral characteristics on the OHRQoL of individuals with MPS (p<0001). The prevalence of malocclusion of individuals with MPS was statistically significant for the oral symptoms, functional limitation, well-being domains and instrument total (p <0.05). We concluded that individuals with MPS have a greater negative impact on the OHRQoL compared to individuals without MPS. The prevalence of malocclusion had a greater impact on the OHRQoL of individuals with MPS.